2005
DOI: 10.1242/jeb.01632
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent protein synthesis capacities in Antarctic and temperate (North Sea) fish (Zoarcidae)

Abstract: For an evaluation of effects of seasonal cold acclimation and evolutionary cold adaptation on protein synthesis capacity, the protein synthesis apparatus was isolated from the gills and white muscle of Antarctic eelpout Pachycara brachycephalum and North Sea eelpout Zoarces viviparus. Both species had been acclimated to 0°C (control) and 5°C (Antarctic) and 5°C and 10°C (North Sea control). The translational capacities of the protein synthesis machineries were determined in an optimised cell-free in vitro syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 51 publications
4
30
0
Order By: Relevance
“…2 A), most notably in the coelevation of 29 ribosomal protein genes (Table S3 in SI Appendix). The increase in ribosomal biogenesis suggests enhanced protein synthesis capacity in this tissue, which was reported for the gill and white muscle of another cold-adapted Antarctic teleost, the zoarcid Pachycara brachycephalum (21).…”
Section: Resultssupporting
confidence: 66%
“…2 A), most notably in the coelevation of 29 ribosomal protein genes (Table S3 in SI Appendix). The increase in ribosomal biogenesis suggests enhanced protein synthesis capacity in this tissue, which was reported for the gill and white muscle of another cold-adapted Antarctic teleost, the zoarcid Pachycara brachycephalum (21).…”
Section: Resultssupporting
confidence: 66%
“…3), cycloheximide sensitive respiration was found to be significantly higher in most of the highAntarctic nototheniids than in the sub-Antarctic species, while ouabain sensitive respiration displayed a contrasting trend and was somewhat lower. In the context with earlier observations by other authors, the observed bias in energy allocation may indicate that the stenothermal high Antarctic nototheniids possess greater protein synthesis capacities than the more eurythermal species but lower capacities of active ion regulation: Storch et al (2005) observed higher protein synthesis capacities in the cold-eurythermal Antarctic eelpout P. brachycephalum as compared to the warm-eurythermal common eelpout Zoarces viviparus, and other authors also found evidence for cold compensated protein synthesis in high-Antarctic fish (Smith and Haschemeyer 1980) and sea urchin embryos (Marsh et al 2001). Furthermore, several studies investigating pH and ion regulation in eurythermal and stenothermal fish (Po¨rtner and Sartoris 1999;Bock et al 2001;Sartoris et al 2003a) found the greater part of pH regulation in eurythermal fish to be dependent on active processes like regulation via Na + /K + -ATPase, while in stenothermal fish, less costly passive processes prevailed.…”
Section: Variability In Energy Budgetssupporting
confidence: 51%
“…Indeed, the high RNA/ protein ratio for APEH-2 Tb may represent a possible approach to maintain the capability for an immediate response to the oxidative environment when the levels of damaged proteins become too high. Recently, it has been reported that the Antarctic invertebrates maintain elevated RNA/protein ratios, through increased RNA levels to counterbalance the low RNA translational efficiency at low temperatures; a different strategy has been seen for the Antarctic eelpout (Pachycara brachycephalum), which shows improved RNA translational capacity [42]. However, further studies will be required to determine whether the strategies adopted by Antarctic fish to counteract the lower protein synthesis rates involve an increase in RNA concentration, an enhancement of translational capacity, or a combination of both mechanisms.…”
Section: Discussionmentioning
confidence: 99%